Bone microarchitecture, biomechanical properties, and advanced glycation end-products in the proximal femur of adults with type 2 diabetes - Karim, Lamya; Moulton, Julia; Van Vliet, Miranda; Velie, Kelsey; Robbins, Ann; Malekipour, Fatemeh; Abdeen, Ayesha; Ayres, Douglas; Bouxsein, Mary L. (Bone (New York, N.Y.), 2018)
Skeletal fragility is a major complication of type 2 diabetes mellitus (T2D), but there is a poor understanding of mechanisms underlying T2D skeletal fragility. The increased fracture risk has been suggested to result from deteriorated bone microarchitecture or poor bone quality due to accumulation of advanced glycation end-products (AGEs). We conducted a clinical study to determine whether: 1) bone microarchitecture, AGEs, and bone biomechanical properties are altered in T2D bone, 2) bone AGEs are related to bone biomechanical properties, and 3) serum AGE levels reflect those in bone. To do so, we collected serum and proximal femur specimens from T2D (n = 20) and non-diabetic (n = 33) subjects undergoing total hip replacement surgery. A section from the femoral neck was imaged by microcomputed tomography (microCT), tested by cyclic reference point indentation, and quantified for AGE content. A trabecular core taken from the femoral head was imaged by microCT and subjected to uniaxial unconfined compression tests. T2D subjects had greater HbA1c (+23%, p ≤ 0.0001), but no difference in cortical tissue mineral density, cortical porosity, or trabecular microarchitecture compared to non-diabetics. Cyclic reference point indentation revealed that creep indentation distance (+18%, p ≤ 0.05) and indentation distance increase (+20%, p ≤ 0.05) were greater in cortical bone from T2D than in non-diabetics, but no other indentation variables differed. Trabecular bone mechanical properties were similar in both groups, except for yield stress, which tended to be lower in T2D than in non-diabetics. Neither serum pentosidine nor serum total AGEs were different between groups. Cortical, but not trabecular, bone AGEs tended to be higher in T2D subjects (21%, p = 0.09). Serum AGEs and pentosidine were positively correlated with cortical and trabecular bone AGEs. Our study presents new data on biomechanical properties and AGEs in adults with T2D, which are needed to better understand mechanisms contributing to diabetic skeletal fragility. •Type 2 diabetics have similar cortical and trabecular microarchitecture as non-diabetics in the femoral neck and head.•Reference point indentation measures in cortical bone at the femoral neck are worse in type 2 diabetics than in non-diabetics.•Advanced glycation end-products (AGEs) in bone are not related to bone biomechanical properties at the femoral neck.•Cortical bone AGEs are higher in type 2 diabetics than in non-diabetics.•Serum AGEs and pentosidine are positively, but weakly, correlated with bone AGEs.